'It's Time You Knew: I Too Am a Contemporary…'. (2nd April 2020) - Aizenberg, Mikhail
ABSTRACT: This publication offers four presentations from a roundtable on the poet Osip Mandelstam. Mikhail Aizenberg opens with a consideration of Mandelstam's contemporary relevance to poets as well as scholars and readers, as his writings are a vital component of the ongoing life of Russian poetry. Vladimir Aristov points out the ties between Mandelstam and many other poets before comparing his "Lines on the Unknown Soldier" to Picasso's famous Guernica . Leonid Vidgof also considers Mandelstam as a contemporary poet, underlining among other things the important Jewish elements of his work. Konstantin Komarov's brief final statement rounds out the session with two comments: on the ways Mandelstam is still ahead of today's poets, and on the "dreadful povidentialism" of his famous "Stalin epigram."